2022
DOI: 10.31186/jagrisep.21.2.381-396
|View full text |Cite
|
Sign up to set email alerts
|

DAIRY FARMERS’ GROUP DYNAMICS IN “NEW NORMAL” ADAPTATION (A Study Case in Pujon District)

Abstract: Dairy farming in East Java, particularly in Malang Regency, is supported by several districts such as Karangploso, Ngantang, Ngajum, and Pujon as the dairy production centers. Pujon district is one of the dairy production centers in Malang Regency, reaching 20,411 cattle. This research aims to describe the dairy farmers’ group dynamics condition and determine its group dynamics level. The location was purposively determined by considering the dairy center area in Malang Regency, where the majority population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Findings reveal that majority of the respondents were predominantly male, being 62.5% of the respondents while female only accounted for 37.5%. This is in conformity with Thus et al, (2022) which revealed that majority of the farmers are male, and that the Female's role in livestock activities is to help ease men's work due to the heavy labour required in it. Also, this may be as a result of an extra effort in making additional income to cater for the family as stated by Fadimu et al (2020).…”
Section: Selected Personal and Enterprise Characteristicssupporting
confidence: 65%
“…Findings reveal that majority of the respondents were predominantly male, being 62.5% of the respondents while female only accounted for 37.5%. This is in conformity with Thus et al, (2022) which revealed that majority of the farmers are male, and that the Female's role in livestock activities is to help ease men's work due to the heavy labour required in it. Also, this may be as a result of an extra effort in making additional income to cater for the family as stated by Fadimu et al (2020).…”
Section: Selected Personal and Enterprise Characteristicssupporting
confidence: 65%